2018
DOI: 10.2106/jbjs.17.01024
|View full text |Cite
|
Sign up to set email alerts
|

Sixty Years On: Ponseti Method for Clubfoot Treatment Produces High Satisfaction Despite Inherent Tendency to Relapse

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…This study found that the main reasons for 'drop out' were finding aspects of treatment difficult, especially casting and bracing. Difficulty during bracing has been reported elsewhere [26,27]. However, many dropped out due to wider family circumstances, which prevented returning to clinics.…”
Section: Discussionmentioning
confidence: 95%
“…This study found that the main reasons for 'drop out' were finding aspects of treatment difficult, especially casting and bracing. Difficulty during bracing has been reported elsewhere [26,27]. However, many dropped out due to wider family circumstances, which prevented returning to clinics.…”
Section: Discussionmentioning
confidence: 95%
“…Ponseti stated that "regardless of the mode of treatment, the clubfoot has a stubborn tendency to relapse". 3,17 The maximum follow up period in our study is 25 months. Further follow up is required to assess long term relapse rate.…”
Section: Discussionmentioning
confidence: 93%
“…In a more recent study of 101 patients who had very poor compliance with the bracing protocol, resulting in a 68% relapse rate, 38% underwent a TATT. Yet despite the high relapse rate the majority reported a good functional outcome and were satisfied with the appearance of the foot (11). It should be noted, however, that approximately 15% of patients may develop a second relapse following a TATT (12).…”
Section: Tattmentioning
confidence: 91%